FAKTOR DETERMINAN TAX AVOIDANCE PADA SEKTOR INDUSTRI BARANG KONSUMSI DI BEI TAHUN 2017-2021 - Trihardhani, Kirana; Nahumury, Joicenda; Murni, Nur Suci I Mei; Nita, Riski Aprillia (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
This study aims to explain empirically whether leverage, firm size, fixed asset intensity, institutional ownership and managerial ownership affect tax avoidance. The type of research used in this study using quantitative research method and secondary data sources The population in this study is the consumer non cyclicals goods industry sector which had been registered on Indonesia Stock Exchange (IDX) from the 2017-2021 period. This sampling technique uses panel data regression analysis with the Eviews 10 application to process the data. Purposive sampling method was chosen to determine the number of research samples. During the research period there were 113 companies of consumer non cyclicals goods industry sector which had been enrolled on IDX. Based on the criteria those have been determined, there were 48 companies or a total of 240 samples during the five years of research. The empirical results of this study indicate that fixed assets intensity has a positive and significant effect, institutional ownership and managerial ownership have a negative and significant effect, while leverage and firm size have no effect on tax avoidance. Previous research gaps have pushed this tax avoidance study to be conducted again. Especially at companies of consumer non cyclicals goods industry.